Vanished Open Access Journals; Why Preservation Is Needed / Laakso, M., Matthias, L., & Jahn, N. (2021). Open is not forever: A study of vanished open access journals. Journal of the Association for Information Science & Technology, 72(9), 1099–1112. https://doi.org/10.1002/asi.24460 - Grams, Kathy (Evidence Based Library and Information Practice, 2023)
Objective – To determine the number of open access journals that have vanished from the web and to summarize their publishing lifespan, geographical and disciplinary characteristics.Design – A descriptive research study.Setting – The internet and internet archive.Subjects – Open access journals.Methods – To identify vanished open access (OA) journals, vanished was defined by the authors as “a journal that published at least one volume as immediate OA after which production ceased, and the journal, together with the published full-text documents, disappeared from the web.” If the journal content partially existed, it would be considered as vanished if <50% was available during 12 months of data collection which occurred September 2019–September 3, 2020. In 2020, the OA journal list was created by searching Directory of Open Access Journals (DOAJ), Ulrichsweb Global Serials Directory, and Scopus title lists. The list was cross-referenced with database records from DOAJ from 2010–2012, 2012–2014, and 2014–2019; Ulrichsweb title lists from May 24, 2012, and July 3, 2018; and Scopus title lists from February 2014 and April 2018, to determine the missing titles. Previous research by the primary author and two peers, and previous publications, also contributed to the list of vanished journals. Data was collected manually, and duplicates were removed. Authors searched the Keepers Registry to be sure that the journal content was not preserved or accessible. Only titles with an ISSN number were kept in the final list. The authors then searched indexing databases and Google to find the vanished journal’s website, then accessed the website through the Internet Archive's Wayback Machine to gather the information such as the year founded, last year of publication, last year available online, language, country, affiliation, and academic discipline.Main Results – Authors identified 154 completely vanished journal titles and 20 partially vanished journal titles, to total 174 verified titles. Journals originated from 47 countries; the majority were published in English (n=137), and most were from North America, Europe and Central Asia (n=109). Social sciences and humanities domain represented 52.3% or 91 titles, and the last publication year of most titles occurred between 2010 and 2014 (n=110). The authors estimated the average time of the last published issue to the last available time on the internet to be within 1 year for 68 titles and within 5 years for 144 titles.Conclusion – Although the results represent a small number of the available OA journals at the time of the study (1.2%), it reinforces the authors’ theme that “open is not forever” and raises concern of the potential loss of scholarly work.